Green synthesis of silver nanoparticles using a vitamin C rich phyllanthus emblica extract - Sirirat Mookriang (2018)
Silver nanoparticles were prepared by treating a solution of AgNO 3 dissolved in deionized water with Emblica (Phyllanthus emblica) extract as reducing agent. The factors that affect the synthesis of silver nanoparticles (time, temperature and concentration of silver nitrate and reducing agent) were investigated. The high concentration of silver nitrate and reducing agent showed the higher in concentration of silver nanoparticles. The heating temperature help increase the yield of silver nanoparticles at shorter reaction time. Their structure, shape and size distribution were characterized by UV-vis spectrophotometer, SEM and TEM technique. The UV-vis spectrophotometer show peaks located of silver-Emblica nanoparticle at 430 nm and the particle size of silver-Emblica is 41.2 nm in average diameter determined by TEM. © (2013) Trans Tech Publications, Switzerland.